Increase in body weight is lowered when mice received fecal microbiota transfer from donor mice treated with the AT1 receptor antagonist telmisartan - Freschi, Marco L.; Künstner, Axel; Huber, Gianna; Stölting, Ines; Busch, Hauke; Hirose, Misa; Raasch, Walter (Frontiers in Pharmacology, 2024)
Treatment of rodents with the AT1 blocker (ARB) telmisartan (TEL) has an anti-adipose effect. Among other mechanisms, we also have attributed the anti-adipose action to diet-independent alterations in gut microbiota. Thus, we aimed here to confirm this mechanism by using the fecal microbiota transfer (FMT) approach.Seven weeks after initiating a high-fat diet (HFD), C57BL/6N mice received fecal microbiota for 8 weeks from donor mice by oral gavage, continuing HFD feeding. Stool samples came from mice that were treated with TEL (8mg/kg/d by gavage, 12 weeks), thus remaining lean despite HFD feeding (BL/6>f TEL ), while controls received feces samples from vehicle/HFD-treated obese mice (BL/6>f VEH ). Microbiota of the stool samples from these acceptor mice was analyzed by 16S rRNA gene amplicon sequencing.Weight gain was lower in BL6>f TEL than in BL6>f VEH mice after 3 but not 8 weeks. Energy homeostasis, insulin sensitivity, and body composition did not differ between the two groups. -diversity indicated group differences (F=2.27, p=0.005). Although the Firmicutes/Bacteroides ratio did not differ, abundances of distinct phyla, families, and genera varied. Among others, Ruminococcaceae and Desulfovibrionaceae, Desulfovibrionia uncl., and Lachnospiraceae uncl.